World Health Organization studies on bacteriophage typing of mycobacteria. Subdivision of the species Mycobacterium tuberculosis - Rado, T A; Bates, J H; Engel, H W; Mankiewicz, E; Murohashi, T; Mizuguchi, Y; Sula, L (The American review of respiratory disease, 1975)
The ability of lytic mycobacteriophages to subdivide the species Mycobacterium tuberculosis reliably has been studied using a series of 100 strains isolated from cases of tuberculosis in the Netherlands. Techniques for the propagation and application of the viruses have been standardized, as have the conditions for growth and preparation of bacterial strains. On the basis of lytic results with 11 mycobacteriophages, it is proposed that the species Mycobacterium tuverculosis may be subdivided into at least 3 major phage types, A, B, and C, and into 2 subjects, Ax and A2. The reliability of the individual bacteriophage lytic result has been assessed, and the relationship between phage reliability and the degree of certainty with which a strain may be assigned to a phage type is described. The effect of rigorous standardization of techniques on the reliability of bacteriphage typing is demonstrated, and a standard protocol is proposed.